Spatial Distribution of Sand Fly Vectors and Eco-Epidemiology of Cutaneous Leishmaniasis Transmission in Colombia - Ferro, Cristina (PLoS One, 2015)
BACKGROUND: Leishmania is transmitted by Phlebotominae insects that maintain the enzootic cycle by circulating between sylvatic and domestic mammals; humans enter the cycles as accidental hosts due to the vector’s search for blood source. In Colombia, leishmaniasis is an endemic disease and 95% of all cases are cutaneous (CL), these cases have been reported in several regions of the country where the intervention of sylvatic areas by the introduction of agriculture seem to have an impact on the rearrangement of new transmission cycles. Our study aimed to update vector species distribution in the country and to analyze the relationship between vectors’ distribution, climate, land use and CL prevalence. METHODS: A database with geographic information was assembled, and ecological niche modeling was performed to explore the potential distribution of each of the 21 species of medical importance in Colombia, using thirteen bioclimatic variables, three topographic and three principal components derived from NDVI. Binary models for each species were obtained and related to both land use coverage, and a CL prevalence map with available epidemiological data. Finally, maps of species potential distribution were summed to define potential species richness in the country. RESULTS: In total, 673 single records were obtained with Lutzomyia gomezi, Lutzomyia longipalpis, Psychodopygus panamensis, Psathyromyia shannoni and Pintomyia evansi the species with the highest number of records. Eighteen species had significant models, considering the area under the curve and the jackknife results: L. gomezi and P. panamensis had the widest potential distribution. All sand fly species except for Nyssomyia antunesi are mainly distributed in regions with rates of prevalence between 0.33 to 101.35 cases per 100,000 inhabitants and 76% of collection data points fall into transformed ecosystems. DISCUSSION: Distribution ranges of sand flies with medical importance in Colombia correspond predominantly to disturbed areas, where the original land coverage is missing therefore increasing the domiciliation potential. We highlight the importance of the use of distribution maps as a tool for the development of strategies for prevention and control of diseases.